Effects of migration between Zimbabwe and South Africa since 1990 - Nyarugwe, G. (BUSE, 2022)
Since 1994, South Africa has received an influx of Zimbabwean migrants in search of a better living. However, due to South Africa’s apartheid inspired immigration laws, many of these immigrants are faced with increased difficulty in regularising their stay to realise their immigration dream. This thesis examines South Africa’s immigration legislation and how it negatively impacts the livelihood regimes of Zimbabwean migrants living in South Africa, from a development perspective. Through a critical investigation of South Africa’s immigration policy, literature and document analysis, this thesis argues that the South African government is reluctant to overhaul its restrictive apartheid inspired immigration laws to safeguard its national interests, while covertly concealing its lack of capacity and tact to manage the Zimbabwe migrant situation. The study concludes that South Africa’s immigration policy is outdated and exclusionary at the core. This has had deleterious effects on livelihood regimes of Zimbabwean immigrants as they are unable to access critical resources and services such as healthcare, employment, banking and legal protection due to the precarious nature of their immigration status. South Africa has received an influx of Zimbabwean migrants in search of a better living. However, due to South Africa’s apartheid inspired immigration laws, many of these immigrants are faced with increased difficulty in regularising their stay to realise their immigration dream. This thesis examines South Africa’s immigration legislation and how it negatively impacts the livelihood regimes of Zimbabwean migrants living in South Africa, from a development perspective. Through a critical investigation of South Africa’s immigration policy, literature and document analysis, this thesis argues that the South African government is reluctant to overhaul its restrictive apartheid inspired immigration laws to safeguard its national interests, while covertly concealing its lack of capacity and tact to manage the Zimbabwe migrant situation. The study concludes that South Africa’s immigration policy is outdated and exclusionary at the core. This has had deleterious effects on livelihood regimes of Zimbabwean immigrants as they are unable to access critical resources and services such as healthcare, employment, banking and legal protection due to the precarious nature of their immigration status
Keywords: Immigration laws; Immigrants; South Africa